Robust pole placement design - Lee, Hui Teck (2008)
A new procedure for selecting closed-loop poles in the state feedback controller design is proposed. In the usual state feedback controller design, it is too restrictive to place the closed-loop poles in pre-determined locations. We may not achieve good responses by placing the closed-loop poles in the pre-determined locations especially when the system is subjected to uncertain ties. In this project, state feedback control is chosen for the robust analysis of a control problem. We will be specifying desired regions in the s-plane for the closed-loop poles and we will be using iterations to search for an "optimal" controller. The effects of system dynamic changes and parameter variations will also be considered. A robust pole placement procedure will be developed to cater for the parameter variations. Using the proposed method, the closed-loop poles are decided in such a way that they will result in good response. The closed-loop system constructed by this method has the merit of a state feedback pole-placement design and it is a useful technique for designing a robust linear feedback control system.